2003
DOI: 10.1136/jmg.40.12.896
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent de novo mitochondrial DNA mutations in respiratory chain deficiency

Abstract: Starting from a cohort of 50 NADH-oxidoreductase (complex I) deficient patients, we carried out the systematic sequence analysis of all mitochondrially encoded complex I subunits (ND1 to ND6 and ND4L) in affected tissues. This approach yielded the unexpectedly high rate of 20% mutation identification in our series. Recurrent heteroplasmic mutations included two hitherto unreported (T10158C and T14487C) and three previously reported mutations (T10191C, T12706C and A13514G) in children with Leigh or Leigh-like e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 10 publications
6
84
0
Order By: Relevance
“…The T10191C mutation, detected in patient 2 in this study, was first reported in a patient that presented with a progressive Leigh-like clinical picture of epilepsy, strokes, optic atrophy and cognitive decline by Taylor et al 32 Subsequently, several MELAS or LS patients were reported carrying the T10191C mutation. 31,[33][34][35] The clinical features of patient 2 in the present study conformed with typical MELAS but her brain MRI showed lesions in both cerebral cortex and midbrain, suggesting that a diagnosis of MELAS/LS overlap syndrome was more appropriate. Patient 3 presented a similar clinical picture as patient 2, with a final diagnosis of MELAS/LS overlap syndrome based on the combination of clinical manifestations and brain MRI findings.…”
Section: Discussionsupporting
confidence: 63%
“…The T10191C mutation, detected in patient 2 in this study, was first reported in a patient that presented with a progressive Leigh-like clinical picture of epilepsy, strokes, optic atrophy and cognitive decline by Taylor et al 32 Subsequently, several MELAS or LS patients were reported carrying the T10191C mutation. 31,[33][34][35] The clinical features of patient 2 in the present study conformed with typical MELAS but her brain MRI showed lesions in both cerebral cortex and midbrain, suggesting that a diagnosis of MELAS/LS overlap syndrome was more appropriate. Patient 3 presented a similar clinical picture as patient 2, with a final diagnosis of MELAS/LS overlap syndrome based on the combination of clinical manifestations and brain MRI findings.…”
Section: Discussionsupporting
confidence: 63%
“…4,22 The fact that we found no cases with this mutation confirms that it indeed appears a rare cause of complex I deficiency, LS or MELAS syndrome.…”
Section: Discussionsupporting
confidence: 57%
“…In particular, there is a growing number of reports describing ND5 mutations; therefore, this gene appears to be a pathogenic hotspot in these diseases (19 -21). In light of recent reports describing mutations in ND3 (6,7,15), this gene could be another mtDNA hotspot for mutations in pediatric patients with diverse encephalopathies.…”
Section: Discussionmentioning
confidence: 99%